Atypical Transcriptional Regulation and Role of a New Toxin-Antitoxin-Like Module and Its Effect on the Lipid Composition of Bradyrhizobium japonicum - Paul S. Miclea; Mária Péter; Gergely Végh; Gyöngyi Cinege; Ernö Kiss; György Váró; Ibolya Horváth; Ilona Dusha (Molecular Plant-Microbe Interactions, 2010)
A toxin-antitoxin (TA)-like system (designated as bat/bto genes) was identified in Bradyrhizobium japonicum, based on sequence homology and similarities in organization and size to known TA systems. Deletion of the bat/bto module resulted in pleiotropic alterations in cell morphology and metabolism. The generation time of the mutant was considerably decreased in rich media. Atomic force microscopy revealed the modified shape (shorter and wider) and softness of mutant cells. The synthesis of phosphatidylcholine was completely blocked in the mutant bacteria, and vaccenic acid, the predominant fatty acid of membranes of the wild-type cell, was replaced by palmitic acid in the mutant membranes. The mutant bacteria synthesized incomplete lipopolysaccharide molecules. Remarkable changes in the membrane lipid composition may explain the observed morphological alterations and growth properties of the mutant bacteria. The overlapping promoter region of bat/bto and glpD (coding for the aerobic sn-glycerol-3-phosphate dehydrogenase) genes suggests a complex regulation and the involvement of bat/bto in the control of main metabolic pathways and an important role in the maintenance of a normal physiological state of B. japonicum. These data reveal new aspects of the role of TA systems in bacteria.